Upaya Pengendalian Kualitas Produk Tahu Pada UMKM Tahu Prapto Menggunakan Metode Six Sigma Dan Re-Layout - Tutur Wisnu Wardana; Ayudyah Eka Apsari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Tofu Prapto MSMEs are tofu producers who often experience quality problems in the tofu they produce. Based on the data obtained, it shows that the amount of tofu production is 8,400 pcs (100%) and product defects of 1,009 pcs (12%) that occur in Tofu Prapto MSMEs during September 2023.This research will be carried out an analysis of quality control of Tofu defective products in Tofu Prapto MSMEs using the Six Sigma method and Re-Layout Design. By implementing the six sigma method and Re-Layout Design, it is expected to identify defects and provide recommendations for improvement to MSMEs Tahu Prapto.The factor causing the highest defect in the type of dirty tofu defect is caused by there are stations that are too close together such as boiling stations too close to the filtering and printing station in the production process so that dust and dirt from burning wood fuel when The boiling process can stick to the filtering and printing process so that there needs to be a distance between work stations from each other. From the sigma calculation, the average DPMO value is 120119,048 with a sigma value of 2.68 from the sigma calculation results, it can be said that the sigma value is still far from the desired sigma value, which is 6.